Dialect language environment as a prerequisite for the rise emergence of communicative deviancy in junior schoolchildren younger students - Mykhailo Kovalchuk; Nataliia Serhiienko (Vasyl Stefanyk Precarpathian National University, 2017)
The article describes the communication problems of pupils of primary school age due tothe influence of dialect speech broadcast. The main language and dialect causes and ways toeliminate address the communicativeon failures of primary schoolchildren in moderneducational process have been determined. Key words: communication, communicativeon deviance, communicativeon failures,dialect culture, dialecticism, primary school, preschool training preparation.